Influence of exercise on quantity and deformability of immune cells in multiple sclerosis - Proschmann, Undine; Shalchi-Amirkhiz, Puya; Andres, Pauline; Haase, Rocco; Inojosa, Hernán; Ziemssen, Tjalf; Akgün, Katja (Frontiers in Neurology, 2023)
Objective: To investigate the effect of exercise on immune cell count and cell mechanical properties in people with multiple sclerosis (pwMS) on different disease modifying treatments (DMT) versus healthy controls (HC). Methods: A cohort of 16 HC and 45 pwMS, including patients with lymphopenia (alemtuzumab, fingolimod) as well as increased lymphocyte counts (natalizumab), was evaluated for exercise-mediated effects on immune cell counts and lymphocyte deformability. As exercise paradigms, climbing stairs at normal speed or as fast as possible and cycling were used while blood samples were collected before, immediately and 20 as well as 60 minutes post exercise. Immune cell subtypes and lymphocyte deformability were analyzed using multicolor flowcytometry and real-time deformability cytometry. Results: An increase in lymphocytes and selected subsets was observed following exercise in HC and all pwMS on different DMTs. Patients with lymphopenia exhibited an increase of absolute lymphocyte counts and immune cell subsets up to just below or into reference range. An increase above the upper limit of reference range was detected in patients on natalizumab. Exercise induced alterations were observable even in low and more pronounced in high intensive physical activities. Lymphocyte deformability was found to be only mild affected by the investigated exercise regimes. Conclusion: PwMS treated with alemtuzumab, fingolimod and natalizumab respond to acute exercise with a comparable temporal pattern characterized by increase of immune cell subsets as HC. The magnitude of response is influenced by exercise intensity. Exercise-mediated effects should be considered when interpreting laboratory values in patients on immunomodulatory therapy. The impact of exercise on biophysical properties should be further elucidated.